The Contemporary Challenge of the Sea: Science, Society, and Sustainability - David M. Karl (Oceanography, 2014)
The ocean covers nearly 71% of the surface of our planet, but it is still largely unexplored despite its fundamental roles in global food production and climate regulation. The most expansive ocean regions, termed subtropical gyres (Figure 1), are the largest ecosystems on Earth, yet we know little about how they are structured, how they function, or how they may respond to stresses imposed on them by human activities. The North Pacific Subtropical Gyre (NPSG) is the largest of these gyres, and it is isolated from other ocean regions by permanent, clockwise-rotating boundary currents. The NPSG is also very old, with present boundaries having been established at least 10 million years ago (McGowan and Walker, 1985). These conditions of great age and isolation create a habitat that is nutrient starved (e.g., nitrate and phosphate) and relatively devoid of photosynthetic microbes called phytoplankton that harvest sunlight and serve as the base of the marine food chain. Although these regions have been termed "oceanic deserts" by analogy to the deserts on land, because of their vast expanse, regions such as the NPSG control global ocean fluxes of carbon and oxygen and therefore sustain planetary habitability. But like many open ocean regions, the NPSG ecosystem is poorly sampled and not well understood.